An EVALUATE ANTIOXIDANT ACTIVITY, PHENOLIC CONTENT AND COLOUR OF INDONESIAN STINGLESS BEE HONEY AND STING BEE HONEY CULTIVATED IN INDONESIA - Mahani; MOHAMMED AHMED, AYAT OMER; NURHADI, BAMBANG (Asian Journal of Pharmaceutical and Clinical Research, 2022)
ABSTRACT Objective: This study's objective was to evaluate the antioxidant activity, phenolic content, and colour of Indonesian stingless and sting bee honey and to assess the correlation between antioxidant, phenolic content, and colour. Methods: The Indonesian bee honey sample's antioxidant activity was measured using d 2,2-diphenyl-1- picrylhydrazyl (DPPH). Folin-Ciocalteu (FC) was used to determine the phenolic content. The colour was determined using a colourimeter. Results: The values of antioxidant activity (IC50) ranged between 3.58 ± 0.03 µg/ml - 64.27 ± 0.13 µg /ml .H.itama sample from South Sumatra has the highest antioxidant activity, followed by A.dorsata from Bangka Belitung , A. cerana from North Sumatra, T. fuscobalteata from West Nusa Tenggara, and T. biroi South Sulawesi. The total phenolic content of samples ranged from 0.0543 ± 0.003 to 0.1760 ± 0.002 mg GAE/g of honey. The samples A. cerana from North Sumatra, T. biroi from South Sulawesi, A.dorsata from Bangka Belitung, and T. fuscobalteata from West Nusa Tenggara presented the highest quantities of total phenolic contents. The L⁎, a⁎ and b⁎ values ranged (3.08 ± 0.1- 56.19 ± 1.2, 0.845 ± 0.03 - 28.57 ± 0.42 and 1.19 ± 0.22 - 56.51 ± 0.9) respectively. Significant correlation between antioxidant activity, colour, and phenolic content, and of Indonesian bee honey. Conclusion: Indonesian bee honey has a different value of antioxidant activity and phenolic content. Differences between Indonesian bee honey samples in terms of type and regions. The dark honey has higher antioxidant activity than light honey. Keywords: Antioxidant, Stingless Bee Honey, Sting Bee Honey, Phenolic, Colour.